Digital literacy impact on the subjective well-being of the region young population - P. Sh. Shikhgafizov; E. V. Konischeva; S. A. Kotlyarov (Цифровая социология)
Digital literacy is a crucial component of professional and life competence in the modern world and an important condition for the subjective well-being of a modern person. The components of digital literacy are numerous and reflect various aspects: from technical skills to the organisation of knowledge transfer, as well as communication. The younger generation acquires skills in using digital interaction content almost from preschool age. In this regard, it becomes important for future adults to assess the impact of their digital literacy level on subjective well-being, as well as on awareness of its application and improvement possibilities. The article provides analysis of a sociological study results aimed at identifying the impact of digital literacy on the subjective well-being of young people. The empirical base includes the results of an online survey conducted on the territory of Kursk and the Kursk region in October-November 2023. The sample totaled 450 respondents. Understanding young people’s ideas about digital literacy and its impact on subjective well-being will make it possible to more specifically define the necessary measures to enhance digital training, promptly meet individual or group requests when organising studying process and improving competence in the field of digital technologies.